Spinal cord injury without radiologic abnormality: an updated systematic review and investigation of concurrent concussion - William P. Dudney; Eric W. Sherburn (Bulletin of the National Research Centre, 2023)
Abstract Study design Systematic review. Objectives The objectives were to systematically review the literature since the most recent systematic reviews for both adult and pediatric spinal cord injuries without radiologic abnormality (SCIWORA) in order to provide an update on the condition’s epidemiology and characteristics and investigate the relationship between SCIWORA and concurrent concussion. Methods A review was conducted according to the 2020 guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The databases PubMed and OvidSP were searched on February 27, 2022. Inclusion criteria were individuals of any age, diagnosis of SCIWORA with or without abnormalities on MRI, and articles published from 2013 to 2014 (adults only) and 2014–present (all ages). Exclusion criteria were any spinal fracture or dislocation, studies that were narrative reviews, letters, book chapters, or editorials. Risk of bias was assessed using tools from the Clinical Advances Through Research and Information Translation Group at McMaster University and the Joanna Briggs Institute. Collected data were synthesized using Microsoft Excel. Results Since the most recent systematic reviews, a total of 61 studies were identified, resulting in 2788 patients with SCIWORA. 69.55% of patients were pediatric, 30.45% adult. The most prevalent reported mechanism of injury was sports-related (39.56%) followed by fall-related (30.01%) and vehicle-related (27.23%). The vast majority of injuries occurred at the level of the cervical spine (82.59%). Of the 61 included studies, only 5 reported cases of concurrent concussion and/or TBI. Discussion Since the most recent previous systematic reviews, there has been a 64% increase in reported cases of SCIWORA, likely as the result of advances in imaging technology and better awareness of SCIWORA. Still, SCIWORA remains a diagnosis most prevalent in children and young adults, the most common cause being sports-related injury. With the pathogenesis of SCIWORA sharing a predisposition to concussion, the significant lack of reporting of SCIWORA with concurrent concussion suggests that there have been missed diagnoses of either SCIWORA with concurrent concussion or vice versa, leading to longer recovery times, unrecognized and/or untreated underlying pathology, and possibly additional unnecessary morbidity. When the diagnosis of either SCIWORA or concussion is suspected, the other should additionally be considered in order to minimize the possible extended recovery time and related comorbidities. Limitations included the prevalence of lower quality studies such as case reports/series, insufficient reporting of study characteristics, and variability among neurologic impairment scales used and how SCIWORA was defined.